NILAI-NILAI PENDIDIKAN ISLAM DALAM KITAB TARBIYATUL ABNA OLEH SYAIKH MUSTHOFA AL ADAWI - Nabila Azra Haqin; Indra Satia Pohan (JURNAL TARBIYAH, 2025)
This research aims to analyze the values of Islamic education contained in the book Tarbiyatul Abna by Syaikh Musthofa Al-Adawi and its relevance in children's education in the modern era. This research uses the library research method, by analyzing the text of the book Tarbiyatul Abna and various related literary sources that support understanding of Islamic education. The main focus of this research is on three aspects of education taught by Shaykh Musthofa Al-Adawi, namely education on faith, worship, and morals. The research results show that the values of Islamic education in Tarbiyatul Abna are very relevant to be applied in children's education today. Faith education that emphasizes monotheism provides a solid spiritual foundation amidst the challenges of globalization. Worship education, such as prayer, fasting, and reading the Koran, helps children maintain discipline and balance between the worldly and the spiritual. Moral education, which teaches honesty, patience and compassion, is very important for forming good moral character. Methods such as example, habituation and wise advice are also effective in the digital era. Overall, the values in Tarbiyatul Abna can be a guide for forming a generation of Muslims who have noble character and are ready to face the challenges of the times.